Scenedesmus dimorphus تأثير بعض العناصر الثقيلة في قيم الامتصاصية لمزارع الطحلب الأخضر - دنيا باهل جدعان; فؤاد منحر علكم (University of Thi-Qar Journal of Science, 2019)
The present study was concerned with the effect of some heavy metals (Lead, Cadmium,Copper, and Zinc) and their toxicity individually on the growth of green alga Scenedesmusdimorphus which belongs to the phylum of Chlorophyta .This was achieved depending on theabsorption values to measure the living biomass of the alga,and then computing the growthaverage and doubling time when exposing the alga to these metals.The effective median concentration EC50 of each of these four metals were also computed.Theconcentrations (15, 20, 25, 30)mg/l of lead were used. Results showed that exposing the alga tothe concentration (30) mg/l caused an acute decrease in growth. The other concentration (15, 20,25)mg/l also led to a gradual decrease in growth. Treating the alga with(0.05, 0.1, 0.5, 1)mg/lconcentration of Cadmium the number of cells decreased in case of three concentration (0.05,0.1, 0.5) mg/l. The decrease in growth was greater and clearer in case of the concentration (1)mg/lconcentration Cadmium.As for Copper the concentrations (0.5, 1, 1.5, 2)mg/l and theconcentration (2)mg/l had the greatest effect in deceasing growth. Results also showed that theconcentration (3)mg/l of zinc had the greatest effect in decreasing the growth on compared withthe other concentration (0.7, 1, 2, 3)mg/l.The toxic effect of cadmium proved greater than that ofzinc copper, and lead in terms of the effective median concentration which indicated (0.23, 0.396,0.35, 6.8) mg/l after treating the alga with lead, cadmium, copper, and zinc for (144) hours.Results were then analyzed statistically by using the variance analysis (ANOVA) and testing thedifference between the treatments according to the Least Significant Difference (LSD)in p> 0.05.